Nanostructured sensors for determination of 3-(3,4-dichlorophenyl)-1,1-dimethylurea based in molecularly imprinted polymers (MIPs) deposited in screen printed carbon nanotubes - Fernández-Cori, R. A.; Morales-Gomero, J. C.; Huayhuas-Chipana, B. C.; Taboada-Sotomayor, M. D P [UNESP]; Ruíz-Montoya, J. G. (The Electrochemical Society, 2015)
A sensor based on molecularly imprinted polymers (MIP) was developed for determination of 3-(3,4-Dichlorophenyl)-1,1- dimethylurea (diuron). The MIP were synthesized by free radical polymerization in wich diuron acted as template, methacrylic acid (MAA) acted as functional monomer and ethylene glycol dimethacrylate (EGDMA) acted as crosslinker. For construction of the sensor, glassy carbon electrode was modified with Nafion® and MIP/NIP (non imprinted polymer) to see the contribution of MIP, as a film, in the diuron recognition. Differential Pulse Voltammetry was used to the quantification of diuron in a range of response 0.4 - 1.2 V in a PBS (pH=8). All parameters affecting the sensor were optimized. The sensor showed a linear response from 1.00x10-5 to 9.616x10-5 M in PBS 0.1 M (pH=8). The limit of detection was 0.58x10-5 mol L-1. The nanostructured sensor was prepared using carbon nanotubes and showed a 4 times greater response than the glassy carbon, showing promising results.